2016
DOI: 10.1111/1365-2664.12774
|View full text |Cite
|
Sign up to set email alerts
|

Habitat drives dispersal and survival of translocated juvenile desert tortoises

Abstract: 1. In spite of growing reliance on translocations in wildlife conservation, translocation efficacy remains inconsistent. One factor that can contribute to failed translocations is releasing animals into poor-quality or otherwise inadequate habitat. 2. Here, we used a targeted approach to test the relationship of habitat features to posttranslocation dispersal and survival of juvenile Mojave desert tortoises Gopherus agassizii. 3. We selected three habitat characteristicsrodent burrows, substrate texture (preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
1
24
1
Order By: Relevance
“…Although tortoise site fidelity and selective foraging within desert washes has been shown in previous studies (Nafus et al. ), our analysis also showed that tortoises were more likely to make longer distance movements in areas where washes were present. The probability of movement declined with the highest values of wash density, which may underlie their preference for smaller stream channels that are 1–2 m wide (Jennings and Berry ).…”
Section: Discussionsupporting
confidence: 56%
“…Although tortoise site fidelity and selective foraging within desert washes has been shown in previous studies (Nafus et al. ), our analysis also showed that tortoises were more likely to make longer distance movements in areas where washes were present. The probability of movement declined with the highest values of wash density, which may underlie their preference for smaller stream channels that are 1–2 m wide (Jennings and Berry ).…”
Section: Discussionsupporting
confidence: 56%
“…Subadults, which typically exhibit shorter movements and smaller home ranges (Farnsworth et al., ), were encountered more frequently than expected near minor roads. Local use areas near minor roads were also relatively steep, rough, and had a relatively larger area classified as wash, characteristics associated with reduced predation risks among subadults (Hagerty et al., ; Nafus, Esque, Averill‐Murray, Nussear, & Swaisgood, ). Additional investigation is needed to improve understanding of the potential influence of minor roads on desert tortoise movement, such as the possibility of concentrating local activity by providing embankments or other structures for burrow creation or increased resource availability (Latch, Boarman, Walde, & Fleischer, ).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge, however, is that these processes must be calibrated to data, for example empirical observations of a species’ habitat use and movement during dispersal (Nafus et al. , Signer and Ovaskainen , Buderman et al. ).…”
Section: Introductionmentioning
confidence: 99%